Characterization of peptides cleaved by plasmin from the C-terminal polymerization domain of human fibrinogen. - Southan,C; Thompson,E; Panico,M; Etienne,T; Morris,HR; Lane,DA (J Biol Chem, 1985)
The C-terminal region of the fibrinogen gamma chain is known to participate in several functional interactions including fibrin polymerization. This part of the molecule is retained on the gamma chain of fragment D (FgD) when fibrinogen is digested by plasmin in the presence of calcium to produce the fragment D-fragment E (FgD X FgE) complex but is lost if FgD is prepared in the absence of calcium. In an attempt to characterize the C-terminal polymerization domain we have used three techniques to examine this further degradation of FgD following the addition of EDTA and plasmin. Analysis of the digestion by sodium dodecyl sulfate-polyacrylamide gel electrophoresis showed a progressive cleavage of the gamma chain to two small remnants. The polymerization-inhibitory activity of the whole digest was studied using acid-solubilized fibrin. A progressive loss of inhibitory activity was associated with gamma chain shortening, reaching greater than a 120-fold reduction at the end of digestion. The cleavage of peptides was followed by reverse-phase high performance liquid chromatography and the release of a characteristic peptide triplet was associated with gamma chain cleavage. Manual sequencing, amino acid analysis, and fast atom bombardment mass spectrometry established the three peptides as gamma 303-356, 357-373, and 374-405. These peptides have sequences in common with those peptides recently reported by other investigators to be potent polymerization inhibitors. However, when a mixture of the three peptides was added in a 200-fold molar excess to polymerizing fibrin, no inhibitory activity could be demonstrated. It is concluded that the C-terminal polymerization domain of fibrinogen may be an extended region which includes the sequence gamma 303-405, when this is contiguous with the remainder of the gamma chain.